Influences The Sustainability Of Business Continuity Through Mass Customization On Embroidery Smes In West Bandung Regency - Ludiya, Eka; Mulyani Sari, Rini (International Journal of Science, Technology & Management, 2024)
At this time, MSMEs are an important part of the economy in Indonesia, one of them is in the West Java region. It was recorded that in 2021 the number of MSMEs in West Java was 6,257,390 and West Bandung Regency was the area that experienced a significant increase. The categories of the business are accessories, batik, embroidery, craft, fashion, services/others, convection, culinary, food and drink. However, the covid-19 pandemic has caused business actors, especially the embroidery sector that must be work harder in order to survive in the pandemic era. The lack of entrepreneurial innovativeness in business success is can influence a decrease in sales and the success of a business can be seen from business actors who making mass adjustments in terms of production (mass customization). Therefore, business actors are required to be able to maintain their business. On this research using a descriptive and associative methods. Descriptive research explains that characteristic or gap can be used as a basic to solving business problem. On this research, descriptive research explains characteristic and variable function like entrepreneurial innovativeness, mass customization, and business contuinity. The location of this research is in West Bandung Regency, and the research subject were 70 embroidery business actors in West Bandung Regency. Data collection techniques is using library research, then continued with distributing questionnaires and interview. Data analysis techniques is using path diagrams assisted by SEM-PLS software. The result on this research show that entrepreneurial innovativeness mediated by mass customization has an effect on business continuity.